2013
DOI: 10.1289/ehp.1206127
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Disease from Toxic Waste Sites in India, Indonesia, and the Philippines in 2010

Abstract: Background: Prior calculations of the burden of disease from toxic exposures have not included estimates of the burden from toxic waste sites due to the absence of exposure data.Objective: We developed a disability-adjusted life year (DALY)-based estimate of the disease burden attributable to toxic waste sites. We focused on three low- and middle-income countries (LMICs): India, Indonesia, and the Philippines.Methods: Sites were identified through the Blacksmith Institute’s Toxic Sites Identification Program, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 26 publications
0
40
1
Order By: Relevance
“…Even though our findings with regard to close proximity to dumpsites was inconclusive, previous studies have shown the negative effects of toxic waste sites on the environment and human health [ 70 ] including an increase in respiratory symptoms, reduced lung function [ 71 , 72 ], and spatial associations of an increased risk of certain birth defects [ 73 , 74 , 75 , 76 , 77 , 78 ], low birth weight [ 79 ], and an increased incidence of miscarriages [ 80 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Even though our findings with regard to close proximity to dumpsites was inconclusive, previous studies have shown the negative effects of toxic waste sites on the environment and human health [ 70 ] including an increase in respiratory symptoms, reduced lung function [ 71 , 72 ], and spatial associations of an increased risk of certain birth defects [ 73 , 74 , 75 , 76 , 77 , 78 ], low birth weight [ 79 ], and an increased incidence of miscarriages [ 80 ].…”
Section: Discussioncontrasting
confidence: 67%
“…An appropriate DW is more sensitive when determining DALYs for chronic mercury intoxication because of its relevance for morbidity. For this preliminary analysis, a DW of a comparable condition was used, as was done before e.g., [ 27 , 120 , 121 ]. Alcoholism is considered a confounding variable with mercury studies because it causes similar symptoms [ 7 , 13 , 14 , 32 , 61 ], which might justify using its DW for an approximation.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, researchers evaluated the influence of pollution from the smoke of biomass burning from the neighborhood in low socio economic status localities and found it to be a more significant influencer of internal household pollution due to the open courtyard nature of most houses [8]. Other sources of PM such as smoking indoors, sweeping, dusting, burning of candles and incense sticks in the household, and the impact of nearby roadways and transportation-emissions are also found to be significant household air pollution contributors [7,21,22].…”
Section: External Pollutionmentioning
confidence: 99%